Exploring the role of mobile payment adoption in China: An empirical analysis of Alipay and WeChat Pay - Wei He; Kamal Abubker Abrahim Sleiman; Mohammed A.E. Suliman (Acta Psychologica)
The increasing rise of mobile payment (m-payment) services in China demands academics explore the underlying aspects that determine their success rate. User emotions change M-payment systems since they immediately affect their money management methods. This paper creates a model to study the factors that affect how people accept m-payment by combining feelings of anxiety from Social Cognitive Theory (SCT), Regret Theory, and the Technology Acceptance Model (TAM). Based on an empirical study, this research included 577 users of Alipay and WeChat Pay, who were analyzed using SPSS. Adoption intention to use m-payment depends mostly on expected regret, followed by perceived usefulness (PU) and perceived ease of use (PEOU), while the influence of anxiety does not negatively influence the adoption of the m-payment system. This study emphasizes the important part expected remorse plays and the detrimental effects anxiety has on user acceptance and interaction with mobile payment systems.